(untitled) (Scientific journal of the Fergana State University, 2023)
In this scientific article methodological approaches to the place and role of controlling the quality of educational services in higher educational institutions, setting an effective governmental controlling on the quality of educational and teaching processes in the rapid accelerating condition of economic reforms have been analysed theoretically. Furthermore, the mechanisms of controlling quality in the level of higher educational institutions and evaluating methods of their effectiveness have been given